Impact of Glia Cells in Aging and the Neurological Diseases - Valles, Soraya L.; Alvarez-Gamez, Kenia; Campo-Palacio, Ignacio; Colmena-Zaragoza, Carlos; Iradi, Antonio; Aldasoro, Martin; Vila, Jose M.; Torre, Jack de la; Campos-Campos, Juan; Caballero-Luna, Oscar; Jorda, Adrian (Medical Science: Trends and Innovations Vol. 9, 2025)
Aging is the strongest risk factor for metabolic, vascular and neurodegenerative diseases. As a result, it is associated with a gradual decline in cognitive and motor functions. Glia is the first cell to change with aging. Glial cells constitute around 50% of the total cells in the brain and play key roles in regulating brain homeostasis in health and disease. Within the glia are the astrocytes, oligodendroglia and microglia. Whereas, Microglia cells during aging, neurodegeneration and neuroinflammation show different morphological and transcriptional profiles (related to axonal direction and cell adhesion). Furthermore, expressions of the receptors on the surface and actin formation compared to young are also different. This review delves into the role of glia during aging and the development of the diseases. The susceptibility of different regions of the brain to disease is linked to the overstimulation of signals related to the immune system during aging, as well as the damaging impact of these cascades on the functionality of different populations of microglia present in each region of the brain. Furthermore, a decrease in microglial phagocytosis has been related to many diseases and also has been detected during aging. In this paper, the role of glia in different illnesses, such as Alzheimer’s Disease (AD), Amyotrophic lateral sclerosis (ALS), pain-related disorders, cancer, developmental disorders and the problems produced by opening of the blood brain barrier, was also described. Why is the research community only looking for neuron works? Why don’t we investigate the role of glia in the brain? Many people are thinking about it; let’s see the future of research brain. They will clarify many points planted by this review, such as the role in learning, memory, inflammation and oxidative stress controlling our thinking.